Assessment of cognitive function among adults aged ≥ 60 years using the Revised Hasegawa Dementia Scale: cross-sectional study, Lao People's Democratic Republic - Sengchanh Kounnavong; Manithong Vonglokham; Somphou Sayasone; Vanthanom Savathdy; Emiko Masaki; Ryoma Kayano; Bounfeng Phoummalaysith; Boungnong Boupha; Nobuyuki Hamajima (BMC, 2022)
Abstract Background Rapid population ageing remains an important concern for health, social and economics systems; thus, a broader assessment of cognitive decline among adults aged ≥ 60 years is essential. It is important to regularly collect reliable data through validated and affordable methods from people living in different areas and in different circumstances to better understand the significance of this health problem. This study aimed to identify the prevalence of cognitive impairment and the related risk factors by reassessing the scoring of the Revised Hasegawa Dementia Scale among older adults in the Lao People's Democratic Republic. Methods A community-based cross-sectional investigation was conducted in rural and urban settings in six districts of three provinces in the country from January to July 2020. In total, 2206 individuals aged 60-98 years (1110 men and 1096 women) were interviewed in person using a pretested Lao version of the Revised Hasegawa Dementia Scale and the WHO STEPwise approach to noncommunicable disease (NCD) risk factor surveillance (the STEPS survey tool). The adjusted odds ratios (AORs) and 95% confidence intervals (95% CIs) were estimated using a logistic model. Results The study found that 49.3% (1088/2206) of respondents (39.7% [441/1110] of men and 59.0% [647/1096] of women) had scores associated with some level of cognitive impairment. In addition to age, the following factors were significantly associated with cognitive impairment: having no formal education (AOR = 9.5; 95% CI: 5.4 to 16.8, relative to those with a university education), living in the northern region of the country (AOR = 1.4; 95% CI: 1.1 to 1.9, relative to living in the central region), living in a rural area (AOR = 1.5; 95% CI: 1.2 to 1.8), needing assistance with self-care (AOR = 1.8; 95% CI: 1.2 to 2.7) and being underweight (AOR = 1.5; 95% CI: 1.1 to 2.2). Factors associated with no cognitive impairment among older adults include engaging in moderate-intensity physical activity lasting for 10 minutes and up to 1 hour (AOR = 0.6; 95% CI: 0.5 to 0.8) and for > 1 hour (AOR = 0.6; 95% CI: 0.4 to 0.8). Conclusions Using the Lao version of the Revised Hasegawa Dementia Scale, this study found that more than half of adults aged ≥ 60 years had cognitive impairment, and this impairment was associated with several risk factors. The limitations of this study may include possible overdetection due to the cutoff point for the assessment of cognitive decline used in the Revised Hasegawa Dementia Scale, given that the participants were not familiar with the instrument. However, the study results can be used to help inform health policy in the Lao People's Democratic Republic regarding the urgent need for a routine data collection system and for providing an environment that addresses and reduces the identified risk factors for cognitive decline to mitigate their impact.